Islet-specific T-cell clones from nonobese diabetic mice express heterogeneous T-cell receptors. - Candéias, S (1991)
Nonobese diabetic (NOD) mice spontaneously develop a T-cell-mediated autoimmune disease that is similar in many respects to insulin-dependent diabetes mellitus in humans. T-cell clones that specifically recognize pancreatic islet cell antigens can be derived from NOD mice, and most of these have been diabetogenic upon transfer to healthy recipients. We report herein the sequences of the T-cell receptor alpha and beta chains from four NOD-derived, islet-specific clones. The sequences are quite heterogeneous--in the junctional regions, specifically--so there seems to be little hope for treating this disease with specific anti-T-cell receptor reagents. This result contrasts with the strikingly restricted junctional region sequences reported for the receptors on clones derived from mice with experimental allergic encephalomyelitis, another T-cell-mediated autoimmune disease. We discuss possible explanations for this difference.